Perinatal outcomes of spontaneous single fetal death in monochorionic twin pregnancies: a single-center retrospective study - Deng, Chunyan; Chen, Shiyu; Hu, Qing; Huang, Guiqiong; Wang, Xiaodong; Yu, Haiyan (Frontiers in Medicine, 2025)
ObjectiveThe aim of this study was to investigate the perinatal outcomes of surviving co-twins after spontaneous single intrauterine fetal death (sIUFD) in monochorionic (MC) twin pregnancies and to assess the risk of cerebral injury.MethodsThis retrospective study was conducted on 90 MC twin pregnancies resulting in spontaneous single intrauterine fetal death at our tertiary hospital between January 2012 and December 2023. When termination of pregnancy (TOP) and co-twin deaths were excluded, the patients were subdivided into two groups according to their gestational age (GA) at single fetal death: Group 1, < 24 weeks; Group 2, ≥24 weeks.ResultsThere were 83 MCDAs and seven MCMAs. Among the patients, the gestational age (GA) at single fetal death was 24.0 ± 5.95 weeks (range 14–34+4 weeks), whereas two patients with co-twin late death, 19 patients with TOP, and 69 patients continuing pregnancy (including seven monochorionic monoamniotic twins) were included. Kaplan–Meier survival curve indicated that the risk of neurological damage and/or fetal anemia increases with GA at sIUFD. Meanwhile, ROC curve showed that GA at sIUFD is a predictor of cerebral lesions, and the lowest risk of cerebral damage for the co-twin occurred before 25+6 weeks of gestation. Among the 69 continuing pregnancies, the delivery age was 35.1 ± 3.3 weeks, with 68 live births, and the birth weight was 2,355.0 ± 681.0 g. The rates of preterm birth and NICU admission were 62.3 and 50.7%, respectively. Cerebral injury was detected in 10 neonates, three newborn deaths due to cerebral damage caused by extreme prematurity, and two infants (2.9%) with neurological abnormalities. The neonatal outcomes were compared between GAs at single fetal death < 24 weeks (Group 1, 34 cases) and those at ≥24 weeks (Group 2, 35 cases). The average gestational age at delivery (36.6 ± 3.3 vs. 33.7 ± 2.5, p = 0.000) and birth weight (2,639.5 ± 705.2 g vs. 2,074.9 ± 546.9 g, p = 0.000) were greater in the Group 1. The incidence rates of extreme preterm, late preterm, live birth and neonatal mortality were not significantly different between the two groups. The gestational age of patients with sIUFD was negatively correlated with delivery age, with a Spearman's rho = −0.588** (p = 0.000).ConclusionsGA at sIUFD is a predictor of cerebral lesions, the greater the gestational age of sIUFD is, the higher the risk of brain injury among surviving co-twins. There was a negative correlation between gestational age at sIUFD and delivery age in this study. The prenatal outcomes of surviving co-twin with sIUFD before 24 weeks were better than those after 24 weeks